Retrospective Respect for Education - Male Australian Footballers retrospectively appreciate education post-matriculation - Murray, Ashnil Chandra; Grimley, Michael; Sebastian, Dipu (Journal of Education, Health and Sport, 2019)
Introduction and Purpose: Males who excel at sport whilst still at school trivialize education in favour of sport. This study of 12 male Australian footballers aims to examine the hierarchy between education and sport of Australian footballers. Material and Method: Four rugby league,four rugby union and four Australian Rules footballers underwent life history interviews and showed clear prioristation of sport during school. Results: However, the importance of education post-secondary school was recognized by these footballers. This change in perspective supports current research and extends the research by describing perspectives of Australian Footballers post-secondary school. Summary: These findings are interesting in that they demonstrate the initial ascendancy of sport and the retrospective significance of education over sport.